2005
DOI: 10.4049/jimmunol.175.4.2606
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Stimulates Granulocyte Colony-Stimulating Factor Production via the Prostanoid EP2 Receptor in Mouse Peritoneal Neutrophils

Abstract: G-CSF is a hemopoietic growth factor involved in granulocytic differentiation of progenitor cells. In this study, we investigated the effects of PGE2 on G-CSF production in murine peritoneal neutrophils in vitro and in vivo. PGE2 augmented LPS-primed G-CSF release from peritoneal neutrophils. This augmentation was mimicked by a type E prostanoid receptor (EP)2-selective agonist but not by other EP-specific agonists. Indeed, the effect of PGE2 on G-CSF release was abolished in neutrophils isolated from EP2-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…PGE 2 stimulates IL-1␤ expression in macrophages through activation of adenylate cyclase (Ohmori et al, 1990). Furthermore, PGE 2 accelerates release of IL-6, IL-10, and G-CSF from neutrophils and macrophages via EP 2 and EP 4 receptors (Yamane et al, 2000;Treffkorn et al, 2004;Sugimoto et al, 2005). In this study, we showed that NS-398 significantly decreased mRNA levels of IL-1␤, IL-6, and G-CSF in the exudate leukocytes and that the EP 2 receptor agonist reversed the effect of NS-398 on the cytokine mRNA levels.…”
Section: Discussionsupporting
confidence: 53%
“…PGE 2 stimulates IL-1␤ expression in macrophages through activation of adenylate cyclase (Ohmori et al, 1990). Furthermore, PGE 2 accelerates release of IL-6, IL-10, and G-CSF from neutrophils and macrophages via EP 2 and EP 4 receptors (Yamane et al, 2000;Treffkorn et al, 2004;Sugimoto et al, 2005). In this study, we showed that NS-398 significantly decreased mRNA levels of IL-1␤, IL-6, and G-CSF in the exudate leukocytes and that the EP 2 receptor agonist reversed the effect of NS-398 on the cytokine mRNA levels.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have identified that PGE 2 can positively regulate expression of IL-6, KC, G-CSF, and MIP-1␣ during peritonitis (57)(58)(59). Using a casein-induced model of peritonitis, Sugimoto et al demonstrated that the amounts of PGE 2 are significantly increased in the peritoneal cavity (65). This PGE 2 increase correlated well with increased G-CSF expression, followed by infiltration of neutrophils into the peritoneal cavity; significantly smaller amounts of PGE 2 , G-CSF, and neutrophils were found in the peritoneal cavity after administration of indomethacin.…”
Section: Discussionmentioning
confidence: 91%
“…Of the ϳ8,544 genes represented on the cDNA microarray (Incyte Rat GEM), the genes that showed differential expression values greater than 1.5 or less than Ϫ1.5 were selected (18,23). Similar analysis was repeated independently, and the genes showing similar responses to PGE 2 were regarded as differentially expressed genes.…”
Section: Resultsmentioning
confidence: 99%